1998
DOI: 10.1351/pac199870061169
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric barrier discharges and ozone synthesis

Abstract: Abstract:The discharge structure, development and the transferred charge of dielectric barrier discharges (DBD) in arrangements with a gas gap (volume discharge, VD) and in such with pure surface discharges (SD) are compared. On the basis of the properties of DBD some parameters influencing efficiency and ozone production like field strength distribution and energy density are discussed. An explanation for observed unexpected low ozone yields in air-fed SD generators is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 0 publications
5
43
0
1
Order By: Relevance
“…The DBD in volume configuration has been adopted for atmospheric-pressure plasma processing at first for its simple design [3,17,18]. The main drawback of the volume DBD lies in the limited thickness of processed material, as follows from its design.…”
Section: Introductionmentioning
confidence: 99%
“…The DBD in volume configuration has been adopted for atmospheric-pressure plasma processing at first for its simple design [3,17,18]. The main drawback of the volume DBD lies in the limited thickness of processed material, as follows from its design.…”
Section: Introductionmentioning
confidence: 99%
“…Ozone generation efficiency has been widely studied in laboratory conditions and performance has been reported for systems based on pulsed corona discharges and various dielectric barrier discharges [4][5][6][7][8][9][10][11]. For example, more than 20 years ago, Masuda et al [4] reported a surface continuously AC excited (10 kHz and 10 kV peak-to-peak) dielectric barrier discharge (DBD) ozoniser based on a high-purity alumina ceramic with parallel strip-like discharge electrodes and a grounded water-cooled film-like induction electrode capable of producing ozone concentration as high as 5-10 9 10 4 ppm.…”
mentioning
confidence: 99%
“…Using a surface discharge in oxygen at 10 kHz, best result reported by Masuda et al in pure oxygen was a yield of 170 g/kWh [29] with a high level of ozone production of 5 to 10 %. Pietsch in O 2 and in air respectively, using dielectric barrier discharges [30].…”
Section: Ieee Electrical Insulation Magazinementioning
confidence: 99%